Misplaced cochlear implant into the superior semicircular canal - Azevedo, Sara Raquel; Lino, João Vale; Coutinho, Miguel Bebiano; Meireles, Luís (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Cochlear implantation (CI) has become a routine surgery for the treatment of profound hearing-impaired patients all around the world. Surgical complications can occur and are an unexpected medical event related to the procedure itself and causing additional morbidity or a need for a revision surgery. Our goal was to describe a clinical case of a major complication of CI placement and the treatment performed. Our case is about a 68-year-old man proposed for unilateral CI placement. The electrode was placed in the vestibule and semicircular canal requiring surgical revision. This is a rare complication described in literature. Patient gave verbal consent to publish the case.